Carta de Juan R. Meléndez a Emilio S. Belaval - Meléndez, Juan R.; Belaval, Emilio S. (My University, 1966)
Carta relacionada a convocatoria para la sesión ordinaria de la Junta de Gobierno y Agenda
Keywords: Academia de Artes y Ciencias de Puerto Rico; Álvarez Nazario, Manuel; Rivera de Álvarez, Josefina; Figueroa Sanabia, José; Veray, Amaury; Rosa-Nieves, Cesáreo; Martínez Avilés, Emiliano